Non-coding RNAs derived from the foot-and-mouth disease virus genome trigger broad antiviral activity against coronaviruses - Rodríguez-Pulido, Miguel; Calvo-Pinilla, Eva; Polo, Miryam; Saiz, Juan-Carlos; Fernández-González, Raúl; Pericuesta, Eva; Gutiérrez-Adán, Alfonso; Sobrino, Francisco; Martín-Acebes, Miguel A.; Sáiz, Margarita (Frontiers in Immunology, 2023)
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is the causative agent of a potentially severe respiratory disease, the coronavirus disease 2019 (COVID-19), an ongoing pandemic with limited therapeutic options. Here, we assessed the anti-coronavirus activity of synthetic RNAs mimicking specific domains in the non-coding regions of the foot-and-mouth disease virus (FMDV) genome (ncRNAs). These molecules are known to exert broad-spectrum antiviral activity in cell culture, mice and pigs effectively triggering the host innate immune response. The ncRNAs showed potent antiviral activity against SARS-CoV-2 after transfection in human intestinal Caco-2 and lung epithelium Calu-3 2B4 cells. When the in vivo efficacy of the FMDV ncRNAs was assessed in K18-hACE2 mice, administration of naked ncRNA before intranasal SARS-CoV-2 infection significantly decreased the viral load and the levels of pro-inflammatory cytokines in the lungs compared with untreated infected mice. The ncRNAs were also highly efficacious when assayed against common human HCoV-229E and porcine transmissible gastroenteritis virus (TGEV) in hepatocyte-derived Huh-7 and swine testis ST cells, respectively. These results are a proof of concept of the pan-coronavirus antiviral activity of the FMDV ncRNAs including human and animal divergent coronaviruses and potentially enhance our ability to fight future emerging variants.